(untitled) (Semiárida, 2020)
Three years of modem pollen rain have been studied in the Parque Nacional Lihue Calel (La Pampa. Argentina) with Tauber traps. This study provides the interannual and seasonal variations in the pollen concentration, richness and diversity. Microscope analysis reveals 106 pollen types and 53 familias. The pollen spectra show the vegetation type of the Monte and it also shows local Pleridophyta spores. The Chenopodiaceae-Amaranthaceae represents the aloctone flora of surrounding regions of the Parle The first year had an atypical high pollen concentration. This was correlated with an abundant precipitation in the precedent winter. The seasonal pollen spectra showed a good correlation with flowering time of diverse species and with the pollen resources. Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Presentado en la Asociación Paleontológica Argentina. Publicación Especial 6. X Simposio Argentino de Paleontología